Different interaction modes for the default mode network revealed by resting state functional magnetic resonance imaging. (7th December 2015) - Zuo, Nianming; Song, Ming; Fan, Lingzhong; Eickhoff, Simon B.; Jiang, Tianzi
Abstract: The default mode network (DMN), which, in the resting state, is in charge of both the brain's intrinsic mentation and its reflexive responses to external stimuli, is recognized as an essential network in the human brain. These two roles of mentation and reflexive response recruit the DMN nodes and other task networks differently. Existing research has revealed that the interactions inside the DMN (between nodes within the DMN) and outside the DMN (between nodes in the DMN and nodes in task networks) have different modes, in terms of both strength and timing. These findings raise interesting questions. For example, are the internal and external interactions of the DMN equally linear or nonlinear? This study examined these interaction patterns using datasets from the Human Connectome Project. A maximal information‐based nonparametric exploration statistics strategy was utilized to characterize the full correlations, and the Pearson correlation was used to capture the linear component of the full correlations. We then contrasted the level of linearity/nonlinearity with respect to the internal and external interactions of the DMN. After a brain‐wide exploration, we found that the interactions between the DMN and the sensorimotor‐related networks (including the sensorimotor, sensory association, and integration areas) showed more nonlinearity, whereas those between the intra‐DMN nodes were similarly less nonlinear. These findings may provide a clue for understanding the underlying neuronal principles of the internal and external roles of the DMN. Abstract : By using the resting state functional MRI data, we have significantly detected nonlinear associations and nonlinearity factors (deviations from linearity) in the resting state fMRI time course. We quantitatively investigated the interactions within the DMN nodes and found that they are less nonlinear compared with the interactions between the DMN and the task positive networks, which are nonlinear. The nonlinear connectivity connected the DMN and the sensorimotor‐related areas, including the orbitofrontal cortex, supramarginal gyrus, temporal pole, and fusiform area. The common functions of these areas that they are in charge of sensory association and integration.